Pragmatic analysis of the oral code of urban public transport ('combi language') in Metropolitan Lima - Loayza Maturrano, Edward Faustino (2011)
This article focuses on study of oral discourse by semantic and pragmatic analysis of the communicative situation and communicative intention of language from work in urban public transport in metropolitan Lima, interpreting the semantic and pragmatic meaning of words and phrases expressed orally in the dialogues of the actors in the work activity. Also, It uses t e hermeneutical method for interpreting the messages of pragmatic and social significance. The results recorded the nature of pragmatic and sociolinguistic reality of this crypto language.